Implementation Of Synergy Of Zis Fund Management In Sharia Banking And Zakat Management Organizations (Opz) For Strengthening The Zakat Ecosystem - Phatriakalista Intan Apsari; Arin Setiyowati; Fatkhur Huda (Universitas Muhammadiyah Sidoarjo, 2022)
In February 2021, Bank Syariah Indonesia or abbreviated as BSI officially operates, BSI is a merger of Bank Syariah Mandiri, Bank BNI Syariah, and Bank BRI Syariah. BSI changed the constellation of Islamic banking in Indonesia, which formed a new pillar of strength for the Islamic economy in Indonesia. In carrying out the social functions of BSI, especially in the realm of zakat, it certainly cannot run alone. This means that it requires both internal and external BSI institutions in managing zakat funds and other Islamic social funds. Zakat management organizations (OPZ) that are partnered include the National Amil Zakat Agency (BAZNAS) as a form of support in encouraging community participation to increase ZIS and to ensure proper distribution of targets to those who really need it. ) and the National Amil Zakat Agency (BAZNAS) collaborated in which this step was taken as a form of enthusiasm from BSI and BAZNAS in an effort to strengthen and distribute the zakat ecosystem and the Love Zakat Movement. This study aims to analyze the synergy between BSI and BAZNAS in managing ZIS funds and implementing the synergy program to improve community welfare. This research was conducted using qualitative research methods, literature study approach (Library Research). The validity of the data using source triangulation, and data analysis techniques using descriptive analysis. The results show that BSI and BAZNAS in their synergy activities have an analysis of strengths and opportunities, and the implementation of synergies carried out by BSI and BAZNAS in supporting the strengthening of ZIS for the welfare of the community and as support for the charity love movement, namely the policy of merging BAZNAS accounts to BSI, ZIS payment features in the BSI Mobile Banking Application, and the BSI company's zakat payments submitted to BAZNAS.